Housing and property markets in Germany 2020. - Schürt, Alexander (My University, 2021)
For a good ten years, the German housing and property markets have been experiencing a strong differentiation with diverse market constellations. Growth and contraction are parallel development paths in Germany's regions. This poses very different challenges for households, businesses, politics and planning. Internal and external migration create very different regional patterns of housing demand. Due to the decreasing average household size, the number of house-holds has increased significantly more than the size of the population. In growing cities and regions, the shortage of building land has led to particularly strong growth in prices. In the coming years, the demand for new construction will remain high in the growth regions. Demographic developments mean that increasing vacancy rates can be expected in shrinking regions. A moderation of price and rent increases for residential property due to the coronavirus pandemic is not yet discernible. Surprisingly, once again there has been a noticeable increase in the number of building permits granted in the first three quarters of 2020.
Keywords: Wohnungsmarkt; Immobilienmarkt; Wohnungsmarktentwicklung; Wohnungsangebot; Wohnungsnachfrage; Immobilienpreis; Wohnungsmiete; Sozialaspekt; Regionale Disparität; Datenerhebung